Question : Find the average of odd numbers from 5 to 1309
Correct Answer 657
Solution & Explanation
Solution
Method (1) to find the average of the odd numbers from 5 to 1309
Shortcut Trick to find the average of the given continuous odd numbers
The odd numbers from 5 to 1309 are
5, 7, 9, . . . . 1309
After observing the above list of the odd numbers from 5 to 1309 we find that the difference between two consecutive terms are equal. This means the list of the odd numbers from 5 to 1309 form an Arithmetic Series.
In the Arithmetic Series of the odd numbers from 5 to 1309
The First Term (a) = 5
The Common Difference (d) = 2
And the last term (ℓ) = 1309
The average of the numbers forming an Arithmetic Series
= The first term (a) + The last term (ℓ)/2
⇒ The average of numbers forming an Arithmetic Series = a + ℓ/2
Thus, the average of the odd numbers from 5 to 1309
= 5 + 1309/2
= 1314/2 = 657
Thus, the average of the odd numbers from 5 to 1309 = 657 Answer
Method (2) to find the average of the odd numbers from 5 to 1309
Finding the average of given continuous odd numbers after finding their sum
The odd numbers from 5 to 1309 are
5, 7, 9, . . . . 1309
The odd numbers from 5 to 1309 form an Arithmetic Series in which
The First Term (a) = 5
The Common Difference (d) = 2
And the last term (ℓ) = 1309
The Average of the given numbers
= Sum of the given numbers/Total number of given numbers
Thus, to find the average of the given numbers, first, we need to find their sum and the total number of given numbers
Finding the number of terms
For an Arithmetic Series, the nth term
an = a + (n – 1) d
Where
a = First term
d = Common difference
n = number of terms
an = nth term
Thus, for the given series of the odd numbers from 5 to 1309
1309 = 5 + (n – 1) × 2
⇒ 1309 = 5 + 2 n – 2
⇒ 1309 = 5 – 2 + 2 n
⇒ 1309 = 3 + 2 n
After transposing 3 to LHS
⇒ 1309 – 3 = 2 n
⇒ 1306 = 2 n
After rearranging the above expression
⇒ 2 n = 1306
After transposing 2 to RHS
⇒ n = 1306/2
⇒ n = 653
Thus, the number of terms of odd numbers from 5 to 1309 = 653
This means 1309 is the 653th term.
Finding the sum of the given odd numbers from 5 to 1309
The sum of all terms (S) in an Arithmetic Series
= n/2 (a + ℓ)
Where, n = number of terms
a = First term
And, ℓ = Last term
Thus, the sum of all terms (S) of the given odd numbers from 5 to 1309
= 653/2 (5 + 1309)
= 653/2 × 1314
= 653 × 1314/2
= 858042/2 = 429021
Thus, the sum of all terms of the given odd numbers from 5 to 1309 = 429021
And, the total number of terms = 653
Since, the average of the given numbers
= Sum of the given numbers/Total number of given numbers
Thus, the average of the given odd numbers from 5 to 1309
= 429021/653 = 657
Thus, the average of the given odd numbers from 5 to 1309 = 657 Answer
Similar Questions
(1) What will be the average of the first 4340 odd numbers?
(2) Find the average of the first 1362 odd numbers.
(3) Find the average of odd numbers from 9 to 1417
(4) Find the average of odd numbers from 11 to 223
(5) Find the average of odd numbers from 7 to 765
(6) Find the average of odd numbers from 5 to 1175
(7) Find the average of odd numbers from 13 to 1115
(8) What is the average of the first 1307 even numbers?
(9) Find the average of odd numbers from 13 to 1379
(10) Find the average of odd numbers from 11 to 525